Global analysis of plasticity in turgor loss point, a key drought tolerance trait - Megan K. Bartlett; Ya Zhang; Nissa Kreidler; Shanwen Sun; Rico Ardy; Kunfang Cao; Lawren Sack (Ecology Letters, 2014)
Many species face increasing drought under climate change. Plasticity has been predicted to strongly influence species' drought responses, but broad patterns in plasticity have not been examined for key drought tolerance traits, including turgor loss or ‘wilting’ point (π tlp ). As soil dries, plants shift π tlp by accumulating solutes (i.e. ‘osmotic adjustment’). We conducted the first global analysis of plasticity in Δπ tlp and related traits for 283 wild and crop species in ecosystems worldwide. Δπ tlp was widely prevalent but moderate (−0.44 MP a), accounting for 16% of post‐drought π tlp . Thus, pre‐drought π tlp was a considerably stronger predictor of post‐drought π tlp across species of wild plants. For cultivars of certain crops Δπ tlp accounted for major differences in post‐drought π tlp . Climate was correlated with pre‐ and post‐drought π tlp , but not Δπ tlp . Thus, despite the wide prevalence of plasticity, π tlp measured in one season can reliably characterise most species' constitutive drought tolerances and distributions relative to water supply.